The outrun ebook A memoir. - Liptrot, Amy (2017)
"It's wild writing: sexy, unguarded, raw, and ardent ... highly recommended."—The Millions After a decade of heavy partying and hard drinking in London, Amy Liptrot returns home to Orkney, a remote island off the north of Scotland. The Outrun maps Amy's inspiring recovery as she walks along windy coasts, swims in icy Atlantic waters, tracks Orkney's wildlife, and reconnects with her parents, revisiting and rediscovering the place that shaped her. A Guardian Best Nonfiction Book of 2016 Sunday Times Top Ten Bestseller New Statesman Book of the Year